2012
DOI: 10.15666/aeer/1002_195206
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Estimation of Leaf Gas Exchange of Ornamental Woody Plant Species

Abstract: Abstract. Instrumental measurements were carried out on urban tolerant Acer, Fraxinus, and Tilia species and varieties in the Buda Arboretum (N 47°28'47.7" E 19°02'19.6") in order to evaluate differences between their photosynthetic and gas exchange performance. Stomatal conductance, transpiration, net photosynthesis and photosynthetic active radiation (PAR) on sample leaves were measured and calculated using the LCi infrared gas analyzer (IRGA). Meanwhile the photosynthetic activity (net CO 2 assimilation) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…But for the intra cellular CO 2 concentration (C i ) the opposite effect was found without significant differences between the two hybrids. This result is in agreement of Forrai et al, (2012) they reported that there are no variations in interacellular CO 2 concentration between species. Adding 90 kg N/efd.…”
Section: A-3 Gas Exchange Parameterssupporting
confidence: 93%
“…But for the intra cellular CO 2 concentration (C i ) the opposite effect was found without significant differences between the two hybrids. This result is in agreement of Forrai et al, (2012) they reported that there are no variations in interacellular CO 2 concentration between species. Adding 90 kg N/efd.…”
Section: A-3 Gas Exchange Parameterssupporting
confidence: 93%
“…The daily trend of net CO 2 assimilation (A) more or less followed the stomatal conductance; similarly to Forrai et al (2012) at maximum level we measured 10-14 μmol•m −2 •s −1 , which rapidly decreased to 2-6 μmol•m −2 •s −1 to the early afternoon hours. Under drought stress the low stomatal conductance strongly controlled the carbon assimilation of Tilia leaves, which resulted significant differences in the daily accumulated carbon gain (Fig 4 .).…”
Section: Discussionsupporting
confidence: 72%
“…A, B and C respectively). The theoretical relationship between T leaf and both g s and transpiration rate (Jones ) has previously been demonstrated experimentally (Prytz et al , Lake and Woodward , Forrai et al , Janka et al ); indeed, T leaf is used to compute total conductance to water vapour in infrared gas analyser (IRGA) systems (Licor Inc.) and is now in widespread use in infrared thermographic screening equipment for water‐related plant traits (Kim et al ).…”
Section: Resultsmentioning
confidence: 98%